1997
DOI: 10.1152/ajprenal.1997.273.5.f739
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the ROMK protein on apical membranes of rat kidney nephron segments

Abstract: The ATP-sensitive, inwardly rectifying K+ channel, ROMK, has been suggested to be the low-conductance ATP-sensitive K+ channel identified in apical membranes of mammalian renal thick ascending limb (TAL) and cortical collecting duct (CCD). Mutations in the human ROMK gene (KIR1.2) have been identified in kindreds with neonatal Bartter’s syndrome. In the present study, we generated polyclonal antibodies raised against both a COOH-terminal (amino acids 252–391) ROMK-maltose binding protein (MBP) fusion protein a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
129
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(151 citation statements)
references
References 21 publications
22
129
0
Order By: Relevance
“…One such example is thought to be the pH-dependent regulation of the renal secretory K ϩ channel, Kir1.1. This channel is found in the apical membrane of the tubular epithelia (15), where it is inhibited by intracellular, but not extracellular, acidification with a pK of 6.8 (16). Mutations in Kir1.1 that alter its pH sensitivity are responsible for inherited forms of antenatal Bartter's syndrome (17).…”
Section: Resultsmentioning
confidence: 99%
“…One such example is thought to be the pH-dependent regulation of the renal secretory K ϩ channel, Kir1.1. This channel is found in the apical membrane of the tubular epithelia (15), where it is inhibited by intracellular, but not extracellular, acidification with a pK of 6.8 (16). Mutations in Kir1.1 that alter its pH sensitivity are responsible for inherited forms of antenatal Bartter's syndrome (17).…”
Section: Resultsmentioning
confidence: 99%
“…It has been previously shown that ammonium transport and the expression of ROMK1, an NKCC2 splice variant, and cldn19 are heterogeneous in the TAL (19,(35)(36)(37). The first description of different TAL cell types was in 1967 by Allen and Tisher (38), who discovered two cell types in rat TAL by means of scanning electron microscopy: R (rough) cells with prominent microvilli and extensive lateral interdigitations and S (smooth) cells generally devoid of extensive microvilli and with less complex lateral interdigitations.…”
Section: Discussionmentioning
confidence: 99%
“…The potassium that enters the cell via this pump is recycled by basolateral potassium transporters. In addition, potassium may also be secreted apically by the renal outer medullary potassium channel (ROMK) and a potassium chloride cotransporter [133]. In addition, NCC modulates transcellular magnesium and calcium reabsorption in the DCT through interaction with the transporters TRPM6 and 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 4 TRVP5, respectively (Figure 1) [16,85].…”
Section: Typical Hallmarks Of Nccmentioning
confidence: 99%